The Effectiveness of Feet Soak with Warm Water and Murottal Al-Qur'an to Reduce Blood Pressure In Hypertensive Patients - Titik Sapartinah; Ana Sundari; Supardi Supardi (JENDELA NURSING JOURNAL, 2023)
Background: hypertension is a public health problem that is often found in developed and developing countries. There have been many managements of hypertension using non-pharmacological therapy because of their few side effects. Moreover, using more than one therapy in several studies has proven effective.Purpose: to determine the effectiveness of feet soak with warm water and murottal Al-Qur'an to reduce blood pressure in hypertensive patients.Methods: this study used Quasy Experiments with Nonequivalent Control Group Design. These samples were 36 respondents. The sampling technique used purposive sampling and the tests used Paired Sample T-Test and Independent Sample T-Test.Results: the results showed that blood pressure before being given combination therapy with feet soak and murottal Al-Qur'an, showed average value 152.33 (systolic) and 94.17 (diastolic), while after being given combination therapy, the average value becomes 135.17 (systolic) and 81.11 (diastolic) means it has decreased with p value = 0.0000.05. In control group, there was no decreased change in diastolic blood pressure (p = 0.100).Conclusion: the combination of feet soak therapy and murrotal Al-Qur'an is effective in reducing systolic and diastolic blood pressure in hypertensive patients. This combination therapy can be applied easily using standard operating procedures that have been made in this study.